INTEGRATING GREEN SKILLS INTO HRM PRACTICES: A KEY TO SUSTAINABLE TALENT MANAGEMENT - Filippos Vakouftsis, David (KNOWLEDGE - International Journal, 2025)
Human resource management (HRM) plays an important role in aligning organizational goals with sustainability objectives, and integrating green skills into HRM practices is essential for driving long term success. This paper explores how HRM can embed green skills development into talent acquisition, training, and performance management as part of a sustainable talent management strategy. Green skills, defined as the abilities and knowledge that contribute to environmental sustainability, are becoming increasingly important as organizations strive to reduce their ecological footprint. Through a review of current literature, the paper investigates the frameworks and best practices for incorporating green competencies into HRM processes, highlighting the role of green skills in shaping recruitment criteria, employee development programs, and performance metrics. Sustainable talent management, which involves nurturing a workforce capable of contributing to environmental and social goals, requires HRM to rethink traditional approaches. By embedding green skills into the employee lifecycle starting with job design and recruitment, followed by training initiatives and ongoing performance evaluation HRM departments can facilitate the development of environmentally conscious talent. This paper argues that green skills serve as the cornerstone of sustainable talent management, enabling companies to achieve both competitive advantage and environmental responsibility. The findings of this paper underscore the need for HRM professionals to adopt a strategic approach that integrates sustainability into core HR functions. Specifically, green skills development consists a key element of HR strategies to meet both organizational sustainability goals and the expectations of an increasingly eco conscious workforce. Furthermore, the research provides recommendations for HRM practices, such as incorporating green competencies into job descriptions, offering sustainability focused training programs, and designing performance management systems that reward green initiatives. By bridging the gap between HRM practices and organizational sustainability goals, this paper contributes to sustainable human resource management knowledge. The recommendations offered provide actionable insights for HR professionals seeking to embed sustainability into their practices, ensuring that organizations can attract, develop, and retain talent that aligns with their environmental and social objectives.